2022
DOI: 10.3390/children9101585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Pacifier Use in Preterm Neonates and Breastfeeding in Infancy: A Systematic Review

Abstract: Background: Breastfeeding is very important for the proper nutrition and growth of the child, as well as, the health of the mother. To start breastfeeding, the neonate must have extensive oral capacities for sucking functions but, premature neonates may not have the muscle strength needed to suck successfully. However, the non-nutritive sucking achieved by using a pacifier, has been identified by previous research as a factor associated with shorter duration and exclusivity of breastfeeding. This study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The risks of reporting the birth experience as 'a little traumatic' or 'very traumatic' and unmet birth expectations was ten times higher after an NELUSCS birth when compared to an ELUSCS birth. This is congruent with the findings of a Greek study where a lack of support and early breastfeeding cessation also contributed to post-traumatic stress [49], and is likely associated with fear and a lack of control that are more commonly experienced with NELUSCS births [50]. It is important that women are screened and offered support for low birth satisfaction, as this is associated with higher risks of postnatal depression and post-traumatic stress disorder [51,52], as well as lower breastfeeding exclusivity and duration rates [53].…”
Section: Discussionsupporting
confidence: 90%
“…The risks of reporting the birth experience as 'a little traumatic' or 'very traumatic' and unmet birth expectations was ten times higher after an NELUSCS birth when compared to an ELUSCS birth. This is congruent with the findings of a Greek study where a lack of support and early breastfeeding cessation also contributed to post-traumatic stress [49], and is likely associated with fear and a lack of control that are more commonly experienced with NELUSCS births [50]. It is important that women are screened and offered support for low birth satisfaction, as this is associated with higher risks of postnatal depression and post-traumatic stress disorder [51,52], as well as lower breastfeeding exclusivity and duration rates [53].…”
Section: Discussionsupporting
confidence: 90%
“…One pediatric association stated that a pacifier assists in the development of hospitalized premature infants, confirmed in a systematic review that attributed pacifier use to weight gain, a better transition from the feeding tube to oral feeding, and earlier discharge [8]. Another advantage reported by two pediatric associations and confirmed in the literature is the contribution of a pacifier to the non-pharmacological management of pain in newborns by diminishing behavioral and physiological responses to pain during medical procedures [33].…”
Section: Discussionmentioning
confidence: 94%
“…Thus, parents incorporate this device as a way to calm a child during moments of agitation or to induce sleep [3,6,7]. Moreover, pacifier sucking has been associated with the oral stimulation of sucking and swallowing reflexes and increases breastfeeding rates for premature newborns when short-term results are observed [8]. Studies have also suggested that pacifier sucking reduces the risk of sudden infant death syndrome (SIDS), which could favor its use [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Non-nutritive sucking using a pacifier during tube feeding was reported to mature and maintain the sucking reflex, improve digestion, provide comfort, and promote neurobehavioral organization (LOE 3) 4,46 . Additionally, systematic reviews concluded that pacifier use in preterm infants helps transition from tube to oral feeding, breastfeeding, faster weight gain, and earlier discharge from the neonatal unit, although the relationship between pacifiers and breastfeeding is more complicated as it appears to be influenced by additional risk factors (LOE 3, GOR C) 47,48 .…”
Section: Pacifier Usementioning
confidence: 99%